Purified CDT toxins and a clean deletion within the CDT locus provide novel insights into the contribution of binary toxin in cellular inflammation and Clostridioides difficile infection. - Kateryna Nabukhotna; Shannon L Kordus; John A Shupe; Rubén Cano Rodríguez; Anna Smith; Julia K Bohannon; M Kay Washington; D Borden Lacy (PLoS Pathogens)
Clostridioides difficile is a spore-forming pathogen and the most common cause of healthcare-associated diarrhea and colitis in the United States. Besides producing the main virulence factors, toxin A (TcdA) and toxin B (TcdB), many of the common clinical strains encode the C. difficile transferase (CDT) binary toxin. The role of CDT in the context of C. difficile infection (CDI) is poorly understood. Inflammation is a hallmark of CDI and multiple mechanisms of inflammasome activation have been reported for TcdA, TcdB, and the organism. Some studies have suggested that CDT contributes to this inflammation through a TLR2-dependent priming mechanism that leads to the suppression of protective eosinophils. Here, we show that CDT does not prime but instead activates the inflammasome in bone marrow-derived dendritic cells (BMDCs). In bone marrow-derived macrophages (BMDMs), the cell binding and pore-forming component of the toxin, CDTb, alone activates the inflammasome and is dependent on K+ efflux. The activation is not observed in the presence of CDTa and is not observed in BMDMs derived from Nlrp3-/- mice suggesting the involvement of the NLRP3 inflammasome. However, we did not observe evidence of CDT-dependent inflammasome priming or activation in vivo. Mice were infected with R20291 and an isogenic CRISPR/Cas9-generated R20291 ΔcdtB strain of C. difficile. While CDT contributes to increased weight loss and cecal edema at 2 days post infection, the relative levels of inflammasome-associated cytokines, IL-1β and IL-18, in the cecum and distal colon are unchanged. We also saw CDT-dependent weightloss in Nlrp3-/- mice, suggesting that the increased weightloss associated with the presence of CDT is not a result of NLRP3-dependent inflammasome activation. This study highlights the importance of studying gene deletions in the context of otherwise fully isogenic strains and the challenge of translating toxin-specific cellular responses into a physiological context, especially when multiple toxins are acting at the same time.